2016
DOI: 10.1016/j.bbadis.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vitamin E against alloxan-induced mouse hyperglycemia

Abstract: It is suggested that the difference in the mice fed vitamin E supplemented diet is due to an increase of insulin secretion and that vitamin E supplementation may have a role in helping to slow the stages of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In terms of glucose regulation, α-tocopherol showed promising hypoglycemic effects in animal studies, by increasing insulin-secreting cells in the pancreas and insulin production, while reducing oxidative products and apoptosis in the pancreas [111,112]. α-tocopherol was less potent as compared to T3 mixture in reducing the plasma glucose or insulin levels in diabetic rats [19,52].…”
Section: Difference In the Metabolic Effect Between T3 And Alpha-tmentioning
confidence: 99%
“…In terms of glucose regulation, α-tocopherol showed promising hypoglycemic effects in animal studies, by increasing insulin-secreting cells in the pancreas and insulin production, while reducing oxidative products and apoptosis in the pancreas [111,112]. α-tocopherol was less potent as compared to T3 mixture in reducing the plasma glucose or insulin levels in diabetic rats [19,52].…”
Section: Difference In the Metabolic Effect Between T3 And Alpha-tmentioning
confidence: 99%
“…Several researchers reported that dietary intake of A. awamori improved an intestinal environment and induced increase of α-tocopherol (vitamin E) level in their blood and muscles to affect the lipid and protein metabolism (El-Deep et al, 2014;Saleh et al, 2013Saleh et al, , 2014. As the intake of vitamin E improved mouse hyperglycemia caused by alloxan and vitamin E improved insulin release from pancreas damaged by alloxan (Kamimura et al, 2013;Takemoto, Doi, & Masuoka, 2016), we deduced that A. awamori is an effective probiotic and increases vitamin E to ameliorate hyperglycemia induced by oxidative stress. Therefore, A. awamori may be likely to be applicable as a supplement if untoward side effects are not observed.…”
Section: Discussionmentioning
confidence: 85%
“…Vitamin E, because of its antioxidant activity, is believed to be promising therapeutic alternative T1DM and T2DM. Supplementation with vitamin E has been reported to ameliorate mouse hyperglycemia through improving secretion of insulin from alloxantreated islet [44]. In vivo, rats with streptozotocin-induced DM were shown to present significant decrease in glucose level and improved antioxidant enzymes activities, including glutathione reductase, glutathione peroxidase, and catalase, after vitamin E supplementation.…”
Section: Vitamin E For T1dm and T2dm Treatmentmentioning
confidence: 99%